Avaliação de tensões residuais de soldagem em chapas planas do aço estrutural ASTM A516 G70 - Oliveira, George Luiz Gomes de (2009)
The main aim of this work was to evaluate the employed welding procedure effect on the level and profile of the final residual stresses on a multipass joint, with emphasis in the welding energy, chamfer and used welding technique. It was also evaluated the effect of the welding current and speed on these stresses, as well as it was correlated the results with microstructure and microhardness. The residual stress measurement was accomplished through X-ray diffraction, using a minidiffractometer for measurement in field. Metallographic analysis was accomplished in the transverse section of the welded joint, using optic microscopy and scanning electron microscopy. It were determined the microhardness profiles in the traverse section of the welded joint. The results showed that the multipass welding residual stresses on the surface of the analyzed samples are compressive in the weld metal and tensile in the HAZ. In the weld root, the welding residual stresses are tensile as in the weld metal as in the HAZ. The welding energy showed a non-linear relationship with the founded residual stresses and it was observed that the most influential parameter was the welding speed, what can be a trouble, since this parameter is the less controlled in manual weldings. The semi-v chamfered samples were the ones that present the fewer levels of residual stresses, due to the stress relief created by plastic deformations during the welding, what do not occur in the X chamfered samples. The double layer technique showed that it can be used in the welding of ASTM A516 Gr70 steel, because, besides promote a refinement and a drawing back of the CG-HAZ, it increased compressive residual stress in the whole surface of the analyzed samples. The founded microstructures and microhardness were similar for all samples and it has believed that the acicular ferrite founded in the weld metal was one of the the main causes for the compressive characteristics of the welding residual stresses in the joints